PROBLEMATIKA PENEGAKAN HUKUM DI INDONESIA - Eman Sulaiman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
Problems of law enforcement in Indonesia is a very serious problem and will continue to grow if the elements in the system itself no change, no reform itself. Indonesian national character is not good is the main actor of incompatibilities implementation of the law in this country. It should be stressed once again, although not all law enforcement in Indonesia is bad. But law enforcement's ugliness seemed to cover any legal alignment that runs in the eyes of society. So many legal cases are alternated in a relatively short period, even at the same event. There needs to be true reform, because of legal issues is fundamental problems of a country, how the public can be secured or how people can feel the actual justice, is the law that governs all of it, and it should be underlined that the law has actually been in accordance with people's lives, but unscrupulous who wants to take advantage of personal and group the originator of all the depravity of law in this country. Needs a lot of evaluations to be done, there must be a follow clear about the fraud law that is increasingly becoming. There needs to be a separate firmness and consciousness hierarchy of individuals or groups involved in it. Need to be instilled a strong mental, embarrassment and the establishment of faith and piety that childhood should be given to the cadres of leaders and implementers of the state apparatus or other interested parties. Due both to the law of Indonesia, is also good for the nation and bad for the law in this country, too bad consequences that will be accepted by society and the State.